Pengembangan Media Video Animasi Pembelajaran Pendidikan Pancasila Berbasis Plotagon Studio dan Capcut Kelas II Sekolah Dasar - Puspitaningrum, Linda; Astutik, Leny Suryaning (JUPEIS : Jurnal Pendidikan dan Ilmu Sosial, 2025)
This research was motivated by the fact that teachers only used lecture methods during learning activities and had no access to engaging visual learning media. The aim of this study was to develop, validate, and assess the practicality of animated video media based on Plotagon studio and CapCut for the subject of Pancasila Education, focusing on the topic Symbols of Religious Diversity for Grade II students at SDI Raudlatul Musthofa. The research employed the ADDIE development model, which includes five stages: Analyze, Design, Develop, Implement, and Evaluate. The instruments used in this study included media expert validation sheets, material expert validation sheets, and questionnaires for teacher and student responses. The results showed that Media Expert 1 gave a validity score of 95.4% ("very valid"), while Media Expert 2 gave 88.6% ("very valid"), with an average media expert score of 92% ("very valid"). Material Expert 1 gave a score of 95.4% ("valid"), and Material Expert 2 gave 96.8% ("very valid"), resulting in an average score of 91.5% ("very valid"). Practicality tests showed that the teacher’s response scored 95.8% ("very practical"), small group trials scored 90% ("very practical"), and field trials scored 95.17% ("very practical")